Circling faith : southern women on spirituality - Reed, Wendy, 1966-; Horne, Jennifer; Adams, Mitzi; Awiakta, Marilou, 1936-; Blackmarr, Amy; Chapman, Marshall; Cushman, Susan, 1951-; Fennelly, Beth Ann, 1971-; Fowler, Connie May; Gibson, Margaret, 1944-; Johnson, Rheta Grimsley, 1953-; Karr, Mary; et al. (University of Alabama Press, 2012)
Circling Faith is a collection of essays by southern women that encompasses spirituality and the experience of winding through the religiously charged environment of the American South. Mary Karr, in "Facing Altars," describes how the consolation she found in poetry directed her to a similar solace in prayer. In "Chiaroscuro: Shimmer and Shadow," Susan Cushman recounts how her dissatisfaction with a Presbyterian upbringing led her to hold her own worship services at home and eventually to join the Eastern Orthodox Church. "Magic" by Amy Blackmarr depicts.